SIMBOL-SIMBOL TRADISI PERKAWINAN MASYARAKAT GALELA, MALUKU UTARA DAN NORWICH, INGGRIS (SUATU ANALISIS SEMIOTIK) - Papo, Satria (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2013)
This study is an attempt to identify and analyze the symbols of wedding as one of the sign systems from semantic point of view. This is intended to contrast the wedding froms of both languages in this case English and Galela. The aspect of this resaearch is related to the sign systems as proposed by Pierce. They are icon, index and symbol. The term of symbol means something which is conventional and accepted by a crtain society, related to what symbolizes. The English data have been collected from several books and websites, whereas the Galela have been taken directly from wedding event and by interviewing the informants to explain what is unknown by writer. The information given by the informants from Tutumaloleo village. The result of research shows that the wedding symbols of both languages have similarities the aim of wedding fuction. The differences of both are as follows : wedding event in English culture is performance in modern style, while in Galela culture it is deeply based in traditional background. The writer hopes that this study will help students in understanding the sign systems especially symbols in building the reassoning systems through sign Keyword: The Traditional Symbols Of Marriage In Galela, North Maluku And Nortwich, England, A Semiotic Analysis.